Optimization of exopolysaccharide production by response surface methodology from Enterococcus faecium isolated from the fermented foods of Western Himalaya - Chauhan, Aditi; Kanwar, Sarbjit Singh (International Journal of Scientific Research in Biological Sciences, 2019)
Eleven potential probiotic bacteria isolated from traditional fermented foods of Western Himalaya were screened for exopolysaccharide production by using ruthenium red milk agar and 3 isolates viz. AdF1, AdF2 and AdF3 were found to be positive. The quantitative analysis of exopolysaccharide production was done by phenol sulphuric acid method where AdF3 showed highest EPS production. For optimization of exopolysaccharide production carbon source, nitrogen source, pH, temperature and incubation time were optimized by using One Variable at a Time approach (OVAT) followed by Response Surface Methodology (RSM). Lactose was found to be the best carbon source (5% for AdF1 and 6% for AdF2 & AdF3) and yeast extract as the best nitrogen source (13.82% for AdF1 and 14.51 % for AdF2 & AdF3). The optimum pH, temperature and incubation time were 6.75, 37ºC and 60 h, respectively for all the isolates. Under optimized conditions, an overall increase of 1.55, 1.37 and 1.42 folds in EPS production was observed with AdF1, AdF2 and AdF3, respectively.